2022
DOI: 10.1002/adma.202200538
|View full text |Cite
|
Sign up to set email alerts
|

All‐Solid‐State Thin Film Lithium/Lithium‐Ion Microbatteries for Powering the Internet of Things

Abstract: As the world steps into the era of Internet of Things (IoT), numerous miniaturized electronic devices requiring autonomous micropower sources will be connected to the internet. All‐solid‐state thin‐film lithium/lithium‐ion microbatteries (TFBs) combining solid‐state battery architecture and thin‐film manufacturing are regarded as ideal on‐chip power sources for IoT‐enabled microelectronic devices. However, unlike commercialized lithium‐ion batteries, TFBs are still in the immature state, and new advances in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 309 publications
2
55
0
Order By: Relevance
“…In the upcoming era of the Internet of Things, miniaturized electronic devices (such as micro sensors, micro robots, medical implants, etc.) will be wirelessly linked together to collect and exchange data, which necessitates the development of compatible micro power sources [1][2][3] . Among current battery technologies, all-solid-state thin film lithium batteries (TFBs) are regarded as the most promising candidate to power these miniaturized electronic devices due to their solid-state architecture, flexible size and shape, long cycle life, low self-discharge rate, and facile miniaturization 2,4,5 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the upcoming era of the Internet of Things, miniaturized electronic devices (such as micro sensors, micro robots, medical implants, etc.) will be wirelessly linked together to collect and exchange data, which necessitates the development of compatible micro power sources [1][2][3] . Among current battery technologies, all-solid-state thin film lithium batteries (TFBs) are regarded as the most promising candidate to power these miniaturized electronic devices due to their solid-state architecture, flexible size and shape, long cycle life, low self-discharge rate, and facile miniaturization 2,4,5 .…”
mentioning
confidence: 99%
“…will be wirelessly linked together to collect and exchange data, which necessitates the development of compatible micro power sources [1][2][3] . Among current battery technologies, all-solid-state thin film lithium batteries (TFBs) are regarded as the most promising candidate to power these miniaturized electronic devices due to their solid-state architecture, flexible size and shape, long cycle life, low self-discharge rate, and facile miniaturization 2,4,5 . Since Bates et al 6 reported the LiCoO2 (LCO)/lithium phosphorus oxynitride (LiPON)/Li TFBs with outstanding electrochemical performance three decades ago, intensive efforts have been made to develop highperformance TFBs [7][8][9] .…”
mentioning
confidence: 99%
See 3 more Smart Citations